Strenghtening the implementation of strategic plan in Hasanuddin University Hospital (HUH) - Nurmala Sari; Ricky Van Kalliecharan (Universitas Aisyiyah Yogyakarta, 2018)
Background: Strategic plan has been recognized as an important tool in management practice as it provides organization framework for decision making, facilitates the measurement of organization changes, and enables the organization to understand where the direction of organization. Various researches indicate that most organization fail to execute their strategy because it is poorly implemented. Hasanuddin University Hospital (HUH) also faced similar challenges. HUH has evaluated its first strategic plan for period of 2010 to 2014 and showed that less than 50% of hospital strategies were implemented. This study aimed to develop strategy to strengthen the implementation of strategic plan in hospital.Methods: The type of the study is an in-depth study using secondary data. Data were obtained from online databases, including Global Health, Medline ovid, Pubmed, NCBI,HMIC, and World Health Organization databases , and also grey literature sources.Result: There are several strategies plan can be considered to be developed as an effort to strengthen strategic plan of HUH which are mobilize all stakeholders to gather in meeting regarding the issue of changing the strategic plan implementation in teaching hospital; creating guideline of strategic plan implementation; redesign Hospital information system as Strategic Information System; and Training of Planning Skill.Conclusion and recommendation: The best strategies to strengthen the HUH plan are establishing the guideline for implementing strategic plan, linking the strategic plan into operational plan, and developing Strategic Information System (SIS). International experience also has been examined to show the various countries that have been successful to adopt those strategies. Based on that analysis, the following recommendations are explained below